Moral Judgment of Children Deprived and Non Deprived of Parental Care in Majd al-Krum and its Relationship to Aggressive Behavior - Hdbawy, Rana Moner; Hamdi, Mohammad Nazeeh (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to investigate moral judgment and its relationship with aggressive behavior among parental care deprived and non- deprived children at Majd Al Krum. The sample of the study consisted of (400) male and female students, of whom (200) parental care deprived children and (200) parental care non- deprived children at Majd Al Krum, Palestine in the 2018/2019 school year. To achieve the aims of the study, the researcher used Moral Judgment Scale developed by Abdel Fattah (2001), while Aggressive Behavior Scale was developed by the researcher. Validity and reliability for both scales were verified.The results of the study revealed low levels of moral judgment among parental care deprived children, while moderate levels of moral judgment were found among parental care non- deprived children at Majd Al Krum. The results of the study indicate high levels of aggressive behavior among parental care deprived children, while low levels of aggressive behavior were found among parental care non- deprived children at Majd Al Krum. There were no statistically significant differences in moral judgment and aggressive behavior level among parental care deprived and non-deprived children at Majd Al Krum due to gender. There were also no statistically significant differences in aggressive behavior among parental care non- deprived children at Majd Al Krum due to class level, while statistically significant differences were found in aggressive behavior among parental care deprived children at Majd al Krum due to class level, in favor of fifth grade students. The results revealed a statistically negative correlation between moral judgment and aggressive behavior among parental care deprived and non- deprived children at Majd Al Krum.Several recommendations and suggestions were presented including the need for future research on this category of children deprived and non deprived of Parental Care in the light of different variables such as emotional intelligence, psychological flexibility, and self-image.
Keywords: Parental Care; Aggressive Behavior; Children; Moral Judgment